Demographic and clinical characteristics of confirmed human monkeypox virus cases in individuals attending a sexual health centre in London, UK: an observational analysis. Issue 9 (September 2022) - Girometti, Nicolò; Byrne, Ruth; Bracchi, Margherita; Heskin, Joseph; McOwan, Alan; Tittle, Victoria; Gedela, Keerti; Scott, Christopher; Patel, Sheel; Gohil, Jesal; Nugent, Diarmuid; Suchak, Tara; et al.
Summary: Background: Historically, human monkeypox virus cases in the UK have been limited to imported infections from west Africa. Currently, the UK and several other countries are reporting a rapid increase in monkeypox cases among individuals attending sexual health clinics, with no apparent epidemiological links to endemic areas. We describe demographic and clinical characteristics of patients diagnosed with human monkeypox virus attending a sexual health centre. Methods: In this observational analysis, we considered patients with confirmed monkeypox virus infection via PCR detection attending open-access sexual health clinics in London, UK, between May 14 and May 25, 2022. We report hospital admissions and concurrent sexually transmitted infection (STI) proportions, and describe our local response within the first 2 weeks of the outbreak. Findings: Monkeypox virus infection was confirmed in 54 individuals, all identifying as men who have sex with men (MSM), with a median age of 41 years (IQR 34–45). 38 (70%) of 54 individuals were White, 26 (48%) were born in the UK, and 13 (24%) were living with HIV. 36 (67%) of 54 individuals reported fatigue or lethargy, 31 (57%) reported fever, and ten (18%) had no prodromal symptoms. All patients presented with skin lesions, of which 51 (94%) were anogenital. 37 (89%) of 54 individuals had skin lesions affecting more than one anatomical site and four (7%) had oropharyngeal lesions. 30 (55%) of 54 individuals had lymphadenopathy. One in four patients had a concurrent STI. Five (9%) of 54 individuals required admission to hospital, mainly due to pain or localised bacterial cellulitis requiring antibiotic intervention or analgesia. We recorded no fatal outcomes. Interpretation: Autochthonous community monkeypox virus transmission is currently observed among MSM in the UK. We found a high proportion of concomitant STIs and frequent anogenital symptoms, suggesting transmissibility through local inoculation during close skin-to-skin or mucosal contact, during sexual activity. Additional resources are required to support sexual health and other specialist services in managing this condition. A review of the case definition and better understanding of viral transmission routes are needed to shape infection control policies, education and prevention strategies, and contact tracing. Funding: None.